2017
DOI: 10.1021/acs.jmedchem.6b01439
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacophore-Based Repositioning of Approved Drugs as Novel Staphylococcus aureus NorA Efflux Pump Inhibitors

Abstract: An intriguing opportunity to address antimicrobial resistance is represented by the inhibition of efflux pumps. Focusing on NorA, the most important efflux pump of Staphylococcus aureus, an efflux pump inhibitors (EPIs) library was used for ligand-based pharmacophore modeling studies. By exploitation of the obtained models, an in silico drug repositioning approach allowed for the identification of novel and potent NorA EPIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 43 publications
2
46
0
Order By: Relevance
“…The lack of information regarding specific interactions between substrates and EPIs with NorA also makes it difficult to rationally design potent inhibitors with computational methods. However, the LBDD approach has been applied successfully in the case of 2‐phenylquinoline derivatives as NorA inhibitors by Sabatini et al They used a library of the most potent NorA EPIs described in the literature to build a pharmacophore model in an attempt to find their common characteristics. The generated pharmacophore model revealed four chemical features of potent NorA EPIs: one H‐bond acceptor, one positive charge, one aromatic ring and one other aromatic ring or hydrophobic region …”
Section: Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of information regarding specific interactions between substrates and EPIs with NorA also makes it difficult to rationally design potent inhibitors with computational methods. However, the LBDD approach has been applied successfully in the case of 2‐phenylquinoline derivatives as NorA inhibitors by Sabatini et al They used a library of the most potent NorA EPIs described in the literature to build a pharmacophore model in an attempt to find their common characteristics. The generated pharmacophore model revealed four chemical features of potent NorA EPIs: one H‐bond acceptor, one positive charge, one aromatic ring and one other aromatic ring or hydrophobic region …”
Section: Future Perspectivesmentioning
confidence: 99%
“…However, the LBDD approach has been applied successfully in the case of 2-phenylquinoline derivatives as NorA inhibitors by Sabatini et al 196,261 They used a library of the most potent NorA EPIs described in the literature to build a pharmacophore model in an attempt to find their common characteristics. The generated pharmacophore To develop high potency inhibitors, it is most appropriate to start from small molecules that possess physicochemical properties according to the "rule of 3" (molecular weight ≤ 300, clogP ≤ 3, rotatable bonds ≤ 3, H-bond donors ≤ 3, H-bond acceptors ≤ 3, PSA ≤ 3), since they are suitable for the process of optimization.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…EtBr will remain in the bacteria, and will emit fluorescence whose intensity will be stable over time. On the other hand, if the compounds do not inhibit the efflux pump, the fluorescence intensity will decrease over time, due to EtBr extrusion by the NorA efflux pump …”
Section: Resultsmentioning
confidence: 99%
“…Multidrug resistant efflux pumps are recognized as important components of resistance in both Gram-positive and Gram-negative bacteria, which reduce the intracellular concentration of drug compounds through active extrusion from the cell (Fern andez & Hancock, 2012;Du et al, 2018). In S. aureus, several multidrug efflux pumps, such as NorA, NorB and MepA, have been described that are associated with resistance to antibiotics, and NorA is the most important and well characterized efflux pump (Holler et al 2012;Astolfi et al, 2017;Felicetti et al, 2017;Felicetti et al, 2018). It is reported that the stable hydrogen bonding interactions between ginsenoside Rh2 (G-Rh2) and Gln51/Asn340/ Ser226 residues at active binding site in the central cavity of protein was responsible for the inhibition of NorA pump, thus G-Rh2 could be used as an inhibitor of the NorA efflux pump to restore susceptibility to common antibiotics in multiple drug resistant (MDR) bacteria (Zhang et al, 2014;Shriram et al, 2018;Kumar et al, 2020).…”
Section: Introductionmentioning
confidence: 99%